Treg Inducing Adjuvants for Therapeutic Vaccination Against Chronic Inflammatory Diseases - Keijzer, Chantal; Van Der Zee, Ruurd; Van Eden, Willem; Broere, Femke (Frontiers in Immunology, 2013)
Many existing therapies in autoimmune diseases are based on systemic suppression of inflammation, the observed side effects illustrate the need for more specific interventions. Regulatory T cells (Treg) are pivotal controllers of (autoaggressive) immune responses, and decreased Treg numbers and/or functioning have been associated with autoimmune disease. Especially antigen-specific targeting of Treg would enable tailor made interventions, while obviating negative side effects of general immuno-suppression. Self-antigens that participate in inflammation, irrespective of the etiology of the different autoimmune diseases, are held to be candidate antigens for such interventions. Rather than tolerance induction to disease inciting self-antigens, which are frequently unknown, general self-antigens expressed at sites of inflammation would allow targeting of disease independent, but inflammatory-site specific, regulatory mechanisms. Preferably, such self-antigens should be abundantly expressed and up-regulated at the inflammatory site. Heat shock proteins show several of these characteristics. The development of antigen-specific Treg inducing vaccines is a major novel goal in the field of immunotherapy in autoimmune diseases. Progress is hampered by the lack of effective antigens and by the fact that other factors such as dose, route and the presence or absence of an adjuvant, turned out to be critical unknowns, with respect to effective induction of Treg. The use of a Treg inducing adjuvant might be required to achieve effective regulatory responses, in the case of ongoing inflammation. Future goals will be the optimization of natural Treg expansion (or the induction of adaptive Treg) without loss of their suppressive function or the concomitant induction of non-regulatory T cells. Here, we discuss the potential use of protein/peptide-based vaccines combined with Treg inducing adjuvants for the development of therapeutic vaccines against chronic inflammatory conditions.